Galanin and its binding sites in the brain of eels submitted to different osmolar conditions - MASINI, MARIA ANGELA; P. PRATO; B. M. UVA (Journal of Experimental Zoology Part A: Comparative Experimental Biology, 2006)
A galanin (GAL)-like peptidergic system was investigated in the brain of Anguilla anguilla subjected to hyperosmolar and hypoosmolar conditions, by using antisera raised against porcine 1-29 GAL. A group of immunoreactive perikaria was identified in the periventricular hypothalamus, in the ventral thalamus, in the pretectal areas and in the optic tectum. Immunoreactive perikaria were present in the nucleus lateralis of the torus semicircularis in seawater (SW) adapted eels, and were absent in the freshwater (FW) adapted eels. Galaninergic fibres were observed in many areas of the brain. The immunoreactive perikaria and fibres, when localised in the same areas, were more strongly labelled and numerous in the SW adapted eels in comparison to the FW adapted animals. GAL-specific binding sites, investigated by autoradiography using iodinated porcine GAL, occurred in several regions of the brain, in particular in the dorsal telencephalon, in the dorsal thalamus and in the torus semicircularis, where a high density of binding sites was observed in the SW adapted eels. Conversely, a higher density of binding sites was observed in the caudal substantia reticularis and in the corpus cerebelli in the FW adapted eels. We conclude that different distributions and intensity in immunoreactive elements occur in response to the two environmental conditions. A galanin (GAL)-like peptidergic system was investigated in the brain of Anguilla anguilla subjected to hyperosmolar and hypoosmolar conditions, by using antisera raised against porcine 1–29 GAL. A group of immunoreactive perikaria was identified in the periventricular hypothalamus, in the ventral thalamus, in the pretectal areas and in the optic tectum. Immunoreactive perikaria were present in the nucleus lateralis of the torus semicircularis in seawater (SW) adapted eels, and were absent in the freshwater (FW) adapted eels. Galaninergic fibres were observed in many areas of the brain. The immunoreactive perikaria and fibres, when localised in the same areas, were more ...